The rate of breast fibroglandular enhancement during dynamic contrast-enhanced MRI reflects response to neoadjuvant therapy. Issue 136 (March 2021) - Virostko, John; Kuketz, Garrett; Higgins, Erin; Wu, Chengyue; Sorace, Anna G.; DiCarlo, Julie C.; Avery, Sarah; Patt, Debra; Goodgame, Boone; Yankeelov, Thomas E.
Highlights: The rate of fibroglandular enhancement in the ipsilateral breast decreases after treatment. Both the rate and intensity of fibroglandular enhancement predict response to neoadjuvant therapy, with higher rate and intensity of enhancement after treatment in women who achieve favorable response. We found no spatial relationship between the rate or relative intensity of fibroglandular enhancement and proximity to the tumor. Abstract: Purpose: This study assesses the rate of enhancement of breast fibroglandular tissue after administration of a magnetic resonance imaging (MRI) gadolinium-based contrast agent and determines its relationship with response to neoadjuvant therapy (NAT) in women with breast cancer. Method: Women with locally advanced breast cancer (N = 19) were imaged four times over the course of NAT. Dynamic contrast-enhanced (DCE) MRI was acquired after administration of a gadolinium-based contrast agent with a temporal resolution of 7.27 s. The tumor, fibroglandular tissue, and adipose tissue were semi-automatically segmented using a manually drawn region of interest encompassing the tumor followed by fuzzy c-means clustering. The rate and relative intensity of signal enhancement were calculated for each voxel within the tumor and fibroglandular tissue. Results: The rate of fibroglandular tissue enhancement after contrast agent injection declined by an average of 29 % over the course of NAT. This decline was present in 16 of the 19 patients in the study. The rate of enhancement is significantly higher in women who achieve pathological complete response (pCR) after both 1 cycle (68 % higher, p < 0.05) and after 3–5 cycles of NAT (58 % higher; p < 0.05). The relative intensity of fibroglandular enhancement correlates with the rate of enhancement (R 2  = 0.64, p < 0.001) and is higher in women who achieve pCR after both 1 cycle and after 3–5 cycles of NAT (p < 0.05, both timepoints). Conclusion: The rate of fibroglandular tissue enhancement declines over the course of therapy, provides novel information not reflected by tumoral measures, and may predict pathological response early in the course of therapy, with smaller declines in enhancement in women who achieve favorable response.